21 Adult ependymoma in England: Incidence, treatment, and outcomes from GlioCova - Kerlann Le Calvez; Radvile Mauricaite; Peter Treasure; Thomas C Booth; Stephen J Price; Andrew Brodbelt; Jonathan J Gregory; Seema Dadhania; Lillie Pakzad-Shahabi; Maureen Dumba; Ingela Oberg; Sally Vernon; et al. (Neuro-Oncology, 2026)
Abstract Introduction England has a long-running system for national cancer data collection. In this work we present data on incidence, treatment and survival in all adult ependymoma patients in England diagnosed between 2013 and 2018. Methods Gliocova uses a linked pseudo-anonymised data set of all adult patients in England diagnosed with a primary brain tumour between 2013 and 2018. We identified all adult patients with an ependymoma based on ICD-10 diagnosis and tumour morphology. Results In the 6-year period of the study (2013-2018 inclusive), 512 patients were diagnosed with an ependymoma in England: (G1: 14 patients; G2: 486; G3: 12). The commonest entity was G2 ependymoma of the spinal cord (304 patients). The national age-standardised incidence was 0.16 adult ependymoma patients per 100,000 per year. Overall, 86% of patients received treatment (87% female vs. 85% male, p = 0.32) with most patients (84%) undergoing either major resection and/or biopsy and 23% also received radiotherapy. Median survival for patients with G3 ependymoma was 26 months. Five-year survival for patients with G2 ependymoma was 82% but only 48% for those with a G3. In this cohort, 14% of patients died, mainly in hospital (57%). Conclusion This is the first national study looking at adult patients diagnosed with ependymomas in England. Ependymoma is very rare, at 3% of the incidence of GBM. Almost 90% of patients received treatment, mainly surgery. Further work will explore patients’ inpatient admissions, the frequency of these, and the length of stay. This work highlights the rarity of ependymoma, and the need for national-level data and research.